2019
DOI: 10.1101/741330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical sleeve gastrectomy lowers kidney SGLT2 expression in the mouse

Abstract: Background: Bariatric surgery has been established to improve insulin sensitivity and glucose clearance, but also increases insulin and glucagon secretion. Each of the above effects have also been observed following treatment with sodium glucose co-transporter 2 (SGLT2) inhibitors. Aim: To determine whether there is an effect of bariatric surgery (Vertical Sleeve Gastrectomy; VSG) on renal SGLT2 expression in mice. Methods: Eighteen lean mice underwent VSG (n=8) or sham (n=9) surgery. Glucose tolerance tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This allowed us to separate marked improvements in insulin secretion from significant weight loss without the need to pair-feed the sham group 44 . Moreover, it corresponds with our previous findings in lean VSG-treated mice that demonstrated no weight difference when compared to sham mice at 4 weeks post-operatively, yet displayed improved glucose tolerance and corresponding insulin secretion curves during an IPGTT 45 . Of note, insulin tolerance tests at week 8 demonstrated that VSG mice had improved insulin sensitivity, an effect previously attributed in humans to rapid and significant enhancement of postoperative hepatic insulin clearance 46 .…”
Section: Discussionsupporting
confidence: 91%
“…This allowed us to separate marked improvements in insulin secretion from significant weight loss without the need to pair-feed the sham group 44 . Moreover, it corresponds with our previous findings in lean VSG-treated mice that demonstrated no weight difference when compared to sham mice at 4 weeks post-operatively, yet displayed improved glucose tolerance and corresponding insulin secretion curves during an IPGTT 45 . Of note, insulin tolerance tests at week 8 demonstrated that VSG mice had improved insulin sensitivity, an effect previously attributed in humans to rapid and significant enhancement of postoperative hepatic insulin clearance 46 .…”
Section: Discussionsupporting
confidence: 91%
“…This incretin hormone has also been shown to increase significantly following VSG, and to regulate glucocorticoid secretion (25,26). We chronically injected a low dose of the GLP-1RA Semaglutide, to avoid significant body weight loss while achieving significantly lower glycemia, in lean mice as previously reported (17). Interestingly, 11β-HSD1 expression was not affected in either the liver or in the adipose tissue (Fig 4C, D) of Semaglutide-treated mice, suggesting that the observed effects are not driven by the reduction in blood glucose or a direct action of GLP-1.…”
Section: Discussionmentioning
confidence: 96%
“…These effects go beyond reductions in adipose tissue mass and weight loss, and numerous studies (11)(12)(13) have attempted to determine the exact pathways involved in order to replicate the bariatric effect in a less invasive way. These changes include substantial improvements in insulin sensitivity and hepatic gluconeogenesis alongside improvements in liver, cardiovascular, pancreatic islet and kidney function (14)(15)(16)(17), pointing to a potential trans-organ communication axis. Importantly, the potential mechanisms investigated include possible changes in the secretion or action of multiple hormones (18,19).…”
Section: Introductionmentioning
confidence: 99%